DAMPAK VARIABEL SALES GROWTH DAN DEBT TO EQUITY RATIO TERHADAP DIVIDEN PAYOUT RATIO PERUSAHAAN FARMASI DI INDONESIA - Zainuddin Zainuddin; Eliana Eliana (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2022)
The purpose of this analysis is to examine the effect of Sales Growth and Debt to Equity Ratio on the Dividend Payout Ratio in pharmaceutical companies in Indonesia. This research was conducted on five pharmaceutical companies listed on the IDX for the 2014-2018 period. Data analysis was carried out using the panel data analysis model, namely by means of the commond effect model. The results of data analysis show that Sales Growth and Debt to Equity Ratio are simultaneously significant at the 10% level, and Sales Growth is partially positive at the 5% level of the Dividend Payout Ratio in pharmaceutical companies in Indonesia. Then, Debt to Equity Ratio is not significant to the Dividend Payout ratio. This indicates that in order to realize the dividend policy, Sales Growth, because when Sales Growth profits can be created which can be realized by paying dividends.